Reversals and Paradoxes: China Miéville's Anti-Language. Issue 3 (2015) - Głaz, Adam
Abstract : China Miéville's Embassytown explores the nature of language through the warped mirror of an alien Language (capitalized). Human language and Ariekei's Language share a number of properties but the latter does not allow its speakers to express anything contrary to fact. Nor does it allow for "real" thinking, which only emerges when the Ariekei transform from Language-speakers to language-speakers. Being an asemantic, asymbolic, non-signifying, and non-metaphorical system of communication, Language is claimed here to be an example of "anti-language" (in a redefined sense), a perversion of the very essence of natural human language. In an analogous, redefined non-evaluative sense, the Ariekei are "anti-humans, " a species lacking the very nature of humanness: free thought.